Suksesi Kepemimpinan Politik Di Negara Demokrasi: Mekanisme, Tantangan, Dan Implikasinya - Muhammad Maulana Nazril; Muhammad Faishal Fadhlurrahman; Lingga Abi Rahman; Surya Sukti (Asosiasi Peneliti dan Pengajar Ilmu Hukum Indonesia, 2024)
This article discusses political leadership with a focus on the meaning of political leadership, legitimacy, structure and function of political leadership and also political leadership succession in democratic countries. The research method uses literature study or literature review. And also in collecting data, we used the Library Research method in the form of (books) and Internet Searching in the form of articles relevant to the theme created as reference material for writers. Furthermore, the aim of writing is to explain the concept of political leadership comprehensively. By referring to political leadership theories, and also providing a better understanding of the phenomenon of political leadership. Even though there are limitations in references and knowledge, the author hopes for constructive feedback and suggestions from readers to improve quality. So the author hopes to provide benefits for readers in understanding more about political leadership and also our reflections if we want to become leaders in the future.